Spatially tunable multiomic sequencing using light-driven combinatorial barcoding of molecules in tissues - Giorgia Battistoni; Sito Torres-Garcia; Chee Ying Sia; Silvia Corriero; Carla Boquetale; Elena Williams; Anna Cregeen; Karolina Wasilewska; Martina Alini; Nicole Hemmer; Shankar Balasubramanian; Benjamin Czech Nicholson; et al. (Proceedings of the National Academy of Sciences, 2026)
Mapping the molecular identities and functions of cells within their spatial context is key to understanding the complex interplay within and between tissue neighborhoods. A wide range of methods have recently enabled spatial profiling of cellular anatomical contexts, some offering single-cell resolution. These use different barcoding schemes to encode either the location or the identity of target molecules. However, all these technologies face a trade-off between spatial resolution, depth of profiling, and scalability. Here, we present B arcoding by A ctivated L inkage of I ndexes (BALI), a method that uses light to write combinatorial spatial molecular barcodes directly onto target molecules in situ, enabling multiomic profiling by next generation sequencing. A unique feature of BALI is that the user can define the number, size, shape, and resolution of the spatial locations to be interrogated, with the potential to profile millions of distinct regions with subcellular precision. As a proof of concept, we used BALI to capture the transcriptome, chromatin accessibility, or both simultaneously, from distinct areas of the mouse brain in single tissue sections, demonstrating strong concordance with publicly available datasets. We also developed an integrated instrument that automates combinatorial barcode writing on tissue sections, enabling high-throughput profiling. BALI therefore combines high spatial resolution, high throughput, compatibility with standard histological pipelines, and workflow accessibility to enable tunable spatial multi-omic profiling.